Selinexor in combination with decitabine in patients with acute myeloid leukemia: results from a phase 1 study. Issue 2 (28th January 2020) - Bhatnagar, Bhavana; Zhao, Qiuhong; Mims, Alice S.; Vasu, Sumithira; Behbehani, Gregory K.; Larkin, Karilyn; Blachly, James S.; Blum, William; Klisovic, Rebecca B.; Ruppert, Amy S.; Orwick, Shelley; Oakes, Christopher; et al.
Abstract: Current treatment options for older and relapsed or refractory (R/R) acute myeloid leukemia (AML) patients are limited and represent an unmet need. Based on preclinical studies showing strong anti-leukemic effects in vivo, this phase I dose-escalation study assessed the safety and preliminary clinical activity of the oral exportin-1 inhibitor, selinexor, in combination with the hypomethylating agent, decitabine 20 mg/m 2, in adults with R/R AML and in older (age ≥ 60) untreated AML patients. There were no protocol-defined dose limiting toxicities. The recommended phase 2 dose of selinexor was 60 mg (∼35 mg/m 2 ) given twice-weekly. Notable grade ≥3 toxicities included asymptomatic hyponatremia (68%), febrile neutropenia (44%), sepsis (44%), hypophosphatemia (36%), and pneumonia (28%). In 25 patients, the overall response rate was 40%. Modification of selinexor to a flat dose of 60 mg, twice-weekly for two weeks after decitabine, improved tolerability of the regimen and demonstrated preliminary clinical activity in poor-risk patients with AML.